2021
DOI: 10.1111/cid.13001
|View full text |Cite
|
Sign up to set email alerts
|

Screw stability of CAD‐CAM titanium and zirconia abutments on different implants: An in vitro study

Abstract: Background Limited information is available regarding the removal torque values (RTVs) of screws of different abutment materials when used with different implants. Purpose To evaluate the effect of implant type and abutment material (zirconia; Zir and titanium; Ti) on the RTVs of abutment screws after cyclic loading. Materials and methods Internal conical connection implants (CC, OsseoSpeed TX) and modified internal conical connection implants (MCC, OsseoSpeed EV) (n = 10) were clamped in resin dies. Zir and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Loosening of the restoration occurred in 4.1% of the cases which is similar to Derksen et al who reported that loosening of the restoration occurred in 4.6% of the cases (screw loosening, n = 1; de‐cementation from the abutment, n = 1). A recent in vitro study showed that the stability of CAD/CAM titanium abutment screws tightened on implants with a conical connection is very high when inserted with a torque of 25 Ncm 30 . In the present study, both screw loosening cases had a relatively high anatomical restoration, making it hard to tighten the restoration to the implant as the screwdriver was only just long enough.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Loosening of the restoration occurred in 4.1% of the cases which is similar to Derksen et al who reported that loosening of the restoration occurred in 4.6% of the cases (screw loosening, n = 1; de‐cementation from the abutment, n = 1). A recent in vitro study showed that the stability of CAD/CAM titanium abutment screws tightened on implants with a conical connection is very high when inserted with a torque of 25 Ncm 30 . In the present study, both screw loosening cases had a relatively high anatomical restoration, making it hard to tighten the restoration to the implant as the screwdriver was only just long enough.…”
Section: Discussionmentioning
confidence: 45%
“…A recent in vitro study showed that the stability of CAD/CAM titanium abutment screws tightened on implants with a conical connection is very high when inserted with a torque of 25 Ncm. 30 In the present study, both screw loosening cases had a relatively high anatomical restoration, making it hard to tighten the restoration to the implant as the screwdriver was only just long enough. The 25 Ncm insertion torque value might have not been reached in those cases which could have contributed to the loosening of the restorations.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, it can be due to micromovements at the implant abutment connection when the prosthesis is loaded. 11 12 17 18 45 The literature stated that when screw is tightened to the recommended value, the RTV will be lower than the applied torque by 7 to 10%. 18 46 After cyclic loading, the RTV was lower than the applied torque in most literature, which is in accordance with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“… 1 5 8 9 10 Loss of preload is a major cause of screw loosening as it is stated that only 10% of the initial torque is transformed to preload while the other 90% is used to overcome the friction between the irregular surfaces of the implant abutment connection. 11 12 Achieving adequate preload results in a clamping force that secures the implant abutment connection. 13 14 With time, screw loosening leads to an unstable superstructure that irritates soft tissues and causes unequal force distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The crown–implant pairs were then mounted on mastication (Hernandez et al, 2008; Jacobs et al, 2022; Mulla et al, 2021; Nasrin et al, 2018; Yilmaz, Batak, et al, 2021; Yilmaz, Çakmak, et al, 2021; Yilmaz, Gouveia, et al, 2021) simulator at a 30‐degree off‐axis from the loading direction (ISO 14801:2007, 2007; Figure 3). A software program (Excel, Microsoft Corp) was used to randomize the specimen positions on the mastication simulator.…”
Section: Methodsmentioning
confidence: 99%